PENGARUH ARANG SEKAM PADA MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) : arang sekam, hasil, jagung manis, pupuk NPK, pertumbuhan. - Vianney, Yohana; Siswadi; Sumarmi, Sumarmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
The purpose of this study was to see how the provision of rice husk charcoal and NPK fertilizer doses affect the growth and yield of sweet corn (Zea mays saccharata Sturt). The research location was Sobokerto Village, Ngemplak District, Boyolali Regency, 156 meters above sea level, lithosol soil. The method used was RAL (Completely Randomized Design) covering 16 treatments where each treatment was repeated 3 times, using 2 types of treatment factors, namely Rice Husk Charcoal (A) and NPK fertilizer dose (N). The types of treatments used were 4 treatments of rice husk charcoal doses, A0 (rice husk charcoal 0gr/polybag), A1 (rice husk charcoal 125gr/polybag), A2 (rice husk charcoal 250gr/polybag), A3 (rice husk charcoal 375gr/polybag), and NPK fertilizer with 4 doses, N0 (NPK fertilizer dose 0gr/polybag), N1 (NPK fertilizer dose 3gr/polybag), N2 (NPK fertilizer dose 6gr/polybag), and N3 (NPK fertilizer dose 9gr/polybag). Data obtained were subjected to statistical analysis using analysis of variance (Anova) and then using the 5% BNT test. The results of the study showed: (1) A2 rice husk charcoal treatment had a significant impact on the number of leaves, plant height, fresh plant stalks, weight of husked cobs, weight of cobs without husks, and length of husked cobs. (2) NPK N3 fertilizer treatment has a significant impact on the number of leaves, plant height, fresh plant stalks, number of cobs, length of cobs with cobs, length of cobs without cobs, weight of cobs with cobs and weight of cobs without cobs. (3) There is no interaction between rice husk charcoal treatment (A) and NPK fertilizer dose (N) on growth and yield of sweet corn plants. (4) Rice husk charcoal treatment A2 gives best growth and yield sweet corn plants, while the best NPK fertilizer dose is obtained in the N3 treatment.